Tindakan Right Heart Catheterization (RHC) pada Indikasi Penyakit Atrial Septal Defect (ASD) Serta Peran Radiografer dalam Penanganannya - I Gusti Ayu Rahayu Wi Utami1; Putu Irma Wulandari; Kusman Kusman (Universitas Pahlawan Tuanku Tambusai, 2023)
Right heart catheterization is an invasive hemodynamic procedure that can be used to directly measure right heart pressure and calculate cardiac output. RHC is also considered to be the gold standard in the measurement of pulmonary artery pressure, in diagnosing increased heart filling pressure. Blood sampling in the intracardiac space measuring saturation among others: SVC (superior vena cava), MPA (main pulmonary artery), High and Low IVC (inferior vena cava), High and Low SVC (superior vena cava), High-Mid-Low RA (right atrium), Mid and Outflow RV (right ventricle), Right and Left PA (pulmonary artery), LV (left ventricle), and Distal Aorta. And additional samples are LA (left atrium) and PV (pulmonary vein). The measured saturation will be calculated using the formula by considering the value of flow ratio, PAR, mix vein, PVR, PARi, PVRi, Qs, Qp. The competency elements in SKKNI are very important to be applied so that radiographers can meet the standards of knowledge, skills and attitudes required by radiographers in carrying out their roles, functions and authorities when carrying out activities in the intervention room. This study is a literature review in which literature exploration is carried out in various databases using keywords such as